Effects of differences in wiping pressure applied by nurses during daily bed baths on skin barrier function, cleanliness, and subjective evaluations. Issue 3 (15th January 2020) - Konya, Issei; Yamaguchi, Shinya; Sugimura, Naotaka; Matsuno, Chiyomi; Yano, Rika
Abstract: Aim: To clarify the actual condition and examine the effects of differences in wiping pressure applied by clinical nurses during daily bed baths on skin barrier function, cleanliness, and subjective evaluations. Methods: For the purposes of the present quasi‐experimental interventional study, "wiping pressure" was defined as the "force applied vertically to the skin surface during bed baths." Two types of bed baths, one using ordinary wiping (pressure: 23–25 mmHg) and the other using weak wiping (pressure: 12–14 mmHg), were performed on the forearms (right and left) of 30 healthy adult men and women, and the effects on transepidermal water loss, stratum corneum hydration, cleanliness, and subjective evaluations were examined. Results: The results showed no differences between ordinary and weak wiping pressure in regard to the effects on skin barrier function and cleanliness. In terms of subjective evaluations, a significant association was seen between wiping pressure and the "sensation of having dirt removed" ( P = .036). Regarding "degree of pain, " some participants reported that the wiping pressure felt "slightly painful" under both conditions (ordinary: 31.1%; weak: 10.7%), while some with sensitive skin reported feeling pain even during weak wiping pressure. Conclusions: The results of the present study suggest that skin assessments should be performed before and after bed baths, and that wiping pressure should be controlled and evaluated while considering the patient's feelings.